(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
After several pioneering studies on Basque-Aquitanian Onomastics, Estudios sobre la onomástica indígena de Aquitania (Joaquín Gorrochategui´s doctoral thesis, published in 1984) has been and still is the keystone on which to build any further study regarding this field of research. The aforementioned person even did several subsequent additions and corrections to his previous work. The intention here is to release briefly some recent findings and to stress the Iberian Peninsula’s testimonies regarding Personal Onomastics and Theonymy.